Exploring the landscape of common actionable molecular markers in colorectal cancer / Li Jing - Li, Jing (2019)
Studies have shown that abnormalities in either KRAS, BRAF genes or microsatellite instability (MSI)/DNA mismatch repair (MMR) affect response to chemotherapy and clinical outcome of colorectal cancer (CRC) patients. However, little literature is available regarding these important biomarkers in Southeast Asian populations. At the same time, their associations with related molecular events, including the important Wnt/β-catenin pathway and the putative CD133-marked stem cells have gained much interest. In this study, we looked at KRAS and BRAF mutations by real-time PCR in a cohort of 30 Malaysian CRC cases. This was extended to look for correlation with nuclear translocation of β-catenin. We also determined the MMR status via immunohistochemistry (IHC) using 4 antibodies (MLH1, PMS2, MSH2 MSH6) in 80 CRCs. Microsatellite instability status was determined by PCR in this cohort using 5 fluorescent microsatellite markers (mononucleotide repeat markers, BAT-25, BAT-26 and dinucleotide repeat markers D5S346, D2S123 and D17S250) and compared with this with detection of MMR status by immunohistochemistry. The presence of CD133- marked stem cells according to the MMR status constituted an extension of the above. KRAS mutation in exons 2, 3 or 4 was detected in 46.7% (14/30) of the primary CRC tested. BRAF V600E mutation was observed in 16.7% (5/30). KRAS mutation was seen in 6/15 (40%) CRC with and 8/15 (53.3%) without β-catenin nuclear translocation (p=0.715). BRAF V600E mutation was observed in 5 of the 15 (33.3%) CRC without βcatenin nuclear translocation but not in any of the 15 (0%) CRC with β-catenin nuclear translocation (p = 0.042). In other words, all the 5 CRC with BRAF V600E mutation did not demonstrate β-catenin nuclear translocation. Of the 80 primary CRCs tested, 66 (82.5%) had proficient DNA mismatch repair (pMMR) while 14 (17.5%) were deficient (dMMR). All dMMRs were found in right-sided CRCs. Among the 73 CRCs in which PCR analysis for MSI could be carried out, MSI-H was found in 11 (15.1%), MSI-L in iv 13 (17.8%) and MSS in 49 (67.1%). dMMR was seen in 72.7% of MSI-H cases (8/11) with pMMR in 93.5% (58/62) of MSI-L/MSS cases. No statistically significant difference was found between IHC and PCR methods in determining microsatellite instability due to deficient DNA mismatch repair in CRC [McNemar p=1.000; κ=0.639 (p<0.001)]. CD133 was expressed in 64 of the 80 CRCs (left: 36/40 vs right: 28/40; p=0.025). Higher frequency of CD133 immunopositivity (87.9%, 58/66 vs 42.9%, 6/14; p<0.001) and scores (mean ± SD: 9.4 ± 5.1 units vs 2.5 ± 3.6 units; p<0.001) were noted in pMMR CRCs compared to dMMR ones. In conclusion, our study shows that the rates of KRAS and BRAF mutations as well as MSI/dMMR status in CRC of Malaysians are similar to most other populations. IHC analysis for dMMR is as useful as using PCR analysis to determine MSI status. β-catenin nuclear translocation was not associated with KRAS mutation in CRC while wild-type BRAF, but not mutant BRAF, appeared to be associated with β-catenin nuclear translocation. Finally, a proficient MMR system appeared to be positively correlated with CD133-marked stem cells in CRC.